Satgas PPKS Dinanti atau Dihindari? Sebuah Pendekatan Preventif - Suhroji Adha; Etty Nurkhayati; Andiko Nugraha Kusuma; Fatoni Fatoni; Titin Nasiatin; Solis Setiyani; Ayu Puspa Wirani; Husnul Khotimah; Siti Nur Aliyah; Dwi Rahmi; Rifki Qamarrulloh; Hofikoh Awaliyah Putri; Suhanah Suhanah; Intan Pristy Shagita Shima; Nabilah Maulidiannisaa (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The approach to preventing sexual violence in the campus environment continues to be a concern, including through the active role of the PPKS Task Force of Faletehan University. One of the efforts made is through socialization activities to the academic community. This article directly describes the dynamics that emerged during the activity, starting from the effectiveness of material delivery, participant responses, to challenges in creating a safe and inclusive discussion space. Forms of sexual violence, as well as the role of the Task Force have been conveyed well. However, communication that tends to be one-way is still an obstacle in encouraging active participation. The responses of the participants were varied, some were actively involved, but some were passive due to cultural factors, discomfort, and lack of trust in the PPKS Task Force. Other challenges arise in efforts to build a psychologically safe space, especially because there is still an imbalance in power relations in the academic environment and stigma against victims. Therefore, the communication approach, ongoing facilitator training, and student involvement from the planning stage are the main recommendations. These results are expected to inspire other campuses in designing a more comprehensive sexual violence prevention strategy and making victims feel safe.